Design and simulation of Lidar based control system for wind turbine - Atif Iqbal; Deng Ying; Faheem Akhter; Manoj Kumar Panjwani; Danish Khan (International Journal of Power Electronics and Drive Systems (IJPEDS), 2021)
Renewable energy sources could be the main contributor to fulfilling the world’s energy requirement. Wind energy is grabbing the world’s attention due to its abundant nature and reliability. Wind energy is a prominent renewable energy source due to its availability and higher reliability. Despite the aforementioned benefits, there are some challenges such as wind measurement and prediction due to the turbulent nature of the wind. Lidar (light detection and ranging) technology is used in wind turbines to preview the wind and act it accordingly. Wind speed along with the direction is measured by the Lidar before it reaches the wind turbine plane and the control system of the wind turbine utilizes this data for optimal results. It enhances the control system along with it optimizes the output power. This paper presents the Lidar simulation model, which previews the wind earlier than the conventional feedback method. The Lidar simulation model is prepared and implemented on the horizontal axis wind turbine. The simulation is performed in GH Bladed at a 2.0 MW wind turbine. The output results are analyzed with the former method. The power extracted, pitch angle, rotor torque obtained from the proposed methodology proves its efficacy.